Combined mechanical and oral antibiotic bowel preparation is associated with prolonged recurrence‐free survival following surgery for colorectal cancer. Issue 7 (26th July 2021) - Zhang, Lindsey M.; Schuitevoerder, Darryl; White, Michael G.; Feldt, Susan; Krishnan, Pranav; Hyman, Neil; Shogan, Benjamin D.
Abstract: Background and Objectives: Recent studies suggest that bacteria influence the pathogenesis of primary colorectal cancer (CRC), yet their role in recurrence after resection is largely unknown. We have discovered that collagenase‐producing bacteria promote cancer recurrence in mice, and that antibiotic bowel decontamination decreases colonization of these same organisms in humans. We hypothesized that preoperative combined mechanical and oral antibiotic bowel preparation would improve disease‐free survival (DFS) in patients undergoing surgery for CRC. Methods: We reviewed a cancer registry of patients treated for CRC at a tertiary center. Patients who received bowel preparation were compared to those that did not via a 1:1‐propensity score matched for follow‐up, age, sex, BMI, stage, location, chemoradiation, infection, anastomotic leak, and blood transfusion. Results: One thousand two hundred and seventy‐nine patients met inclusion criteria. Following propensity score matching, 264 patients receiving bowel prep were matched to 264 patients who did not. Kaplan–Meier estimates showed that patients who received bowel prep had a significantly improved 5‐year DFS compared to those that did not (76.3% vs. 64.2%; p < .01). Cox regression demonstrated that bowel prep was associated with improved DFS (HR, 0.57; 95% CI, 0.37–0.89; p < .01). Conclusion: Combined mechanical and oral antibiotic bowel preparation is independently associated with improved recurrence‐free survival in patients undergoing surgery for CRC.